1999
DOI: 10.1093/qjmed/92.6.327
|View full text |Cite
|
Sign up to set email alerts
|

Lower cardiac mortality in smokers following thrombolysis for acute myocardial infarction may be related to more effective fibrinolysis

Abstract: Smokers have unexplained lower cardiac mortality than non-smokers in the short term following acute myocardial infarction (AMI). We hypothesized that smokers may have enhanced systemic fibrinolysis following thrombolysis. We studied 185 consecutive patients receiving thrombolysis for first AMI. Cardiac mortality at 36 days after thrombolysis was 11.9% (22 deaths). Factors associated with cardiac mortality were: smoking (current 3.4% mortality, previous 11.4%, never 24.2%) (p < 0.001); post-thrombolysis plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
25
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 28 publications
3
25
0
2
Order By: Relevance
“…Actually, this finding is consistent with the data in literature (20)(21)(22). Smoking is associated with a hypercoagulable state, particularly higher fibrinogen, compared to non-smokers (23).…”
Section: Discussionsupporting
confidence: 93%
“…Actually, this finding is consistent with the data in literature (20)(21)(22). Smoking is associated with a hypercoagulable state, particularly higher fibrinogen, compared to non-smokers (23).…”
Section: Discussionsupporting
confidence: 93%
“…Smoking has been associated with increased hematocrit, platelet activation and aggregation, vasoconstriction, increased circulating levels of fibrinogen, thrombin generation, impaired endogenous fibrinolytic capacity, and increased response to clopidogrel. 7,[35][36][37][38] As a result, the pathogenesis of vascular occlusions in smokers may be more because of changes in thrombogenicity than in atherosclerotic plaque rupture or morphology. This may be particularly true in those patients with fewer clinically manifest traditional atherosclerosis risk factors, whereas in nonsmokers, occlusion may be more frequently because of rupture or ulceration of atheromatous plaque with formation of platelet-rich clot.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, some studies have shown that smokers with myocardial infarction (MI) or AIS have lower case fatality than nonsmokers, including subgroups that undergo treatment with thrombolysis. [3][4][5][6][7][8] This phenomenon was described as the smoker's paradox and was first introduced into scientific discourse >25 years ago. [9][10][11][12] The smoker's paradox is one of several reported paradoxes in the cardiovascular literature that include the obesity paradox and the sex paradox.…”
mentioning
confidence: 99%
“…Interestingly, several cardiac studies have revealed that smokers who receive fibrinolytics have better short-term survival after an acute myocardial infarction than nonsmokers exposed to the same treatment [28,29,30,31,32], and a recent analysis of the National Institute of Neurological Disorders and Stroke rt-PA database similarly suggested that smokers who received intravenous thrombolysis following acute ischemic stroke experienced better early outcomes and longer survival through 1 year after treatment than nonsmokers [33]. Against the backdrop of our findings in this study in which smokers fared more poorly than nonsmokers among a cohort of patients, the overwhelming majority of whom were not thrombolysed, the benefits of thrombolysis in smokers may be even more substantial than is currently realized.…”
Section: Discussionmentioning
confidence: 99%